2008
DOI: 10.1090/s0894-0347-08-00613-9
|View full text |Cite
|
Sign up to set email alerts
|

Manifolds with 1/4-pinched curvature are space forms

Abstract: Let ( M , g 0 ) (M,g_0) be a compact Riemannian manifold with pointwise 1 / 4 1/4 -pinched sectional curvatures. We show that the Ricci flow deforms g 0 g_0 to a constant curvature metric. The proof uses the fact, also established in this paper, that positive isotropic curvature is preserved by the Ricci flow in all dimensions. We also rely o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
317
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(323 citation statements)
references
References 29 publications
(63 reference statements)
3
317
0
3
Order By: Relevance
“…Motivated by the result above and the striking differentiable pinching theorem due to Brendle and Schoen [2009], we propose the following question.…”
Section: Questionsmentioning
confidence: 99%
“…Motivated by the result above and the striking differentiable pinching theorem due to Brendle and Schoen [2009], we propose the following question.…”
Section: Questionsmentioning
confidence: 99%
“…In 1991, Chen [9] showed that a point-wise 1/4-pinched 4-manifold is diffeomorphic to a spherical space form. Recently, Brendle and Schoen [10,11] proved a remarkable differentiable pinching theorem for point-wise 1/4-pinched Riemannian manifolds by developing the theory and techniques of Ricci flow [22][23][24]. More recently, Brendle [12] obtained the following useful result.…”
Section: Some Useful Lemmasmentioning
confidence: 99%
“…Recently Böhm and Wilking [3] proved that every manifold with 2-positive curvature operator must be diffeomorphic to a space form. More recently, Brendle and Schoen [6] proved the remarkable differentiable sphere theorem for manifolds with pointwise 1/4-pinched curvatures.…”
Section: Introductionmentioning
confidence: 99%